Aerosol sampling in wet (informal) markets in Vietnam as an early warning screening for avian influenza viruses in poultry - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
A completed study found aerosol sampling might be useful for early warning screening of poultry markets for novel influenza virus detection, such as H7N9.